2021
DOI: 10.3390/ma14123397
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Effect of RFSSW Parameters on Tensile Shear Fracture Load of 7075-T6 Alclad Aluminium Alloy Joints

Abstract: The aim of the investigations was to determine the effect of parameters of refill friction stir spot welding (RFSSW) on the fracture load and failure mechanisms of the resulting joint. RFSSW joints were made in 7075-T6 Alclad aluminium alloy sheets using different welding parameters. The load capacity of joints was determined under tensile/shear loadings. Finite element-based numerical simulations of the joint-loading process were carried out, taking into account the variability of elasto-plastic properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Figure 10 shows the distributions of von Mises equivalent strains in the two fracture modes in the cross-section. Similar to the numerical simulation results of Kubit et al [9], the main strain was mainly distributed at the lap interface and the upper-plate TMAZ/SZ interface (Figure 10(c,i)). However, owing to significant differences in properties of the upper and lower plates, only the upper plate incurred significant strain during the fracture process.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Figure 10 shows the distributions of von Mises equivalent strains in the two fracture modes in the cross-section. Similar to the numerical simulation results of Kubit et al [9], the main strain was mainly distributed at the lap interface and the upper-plate TMAZ/SZ interface (Figure 10(c,i)). However, owing to significant differences in properties of the upper and lower plates, only the upper plate incurred significant strain during the fracture process.…”
Section: Resultssupporting
confidence: 87%
“…With the global shortage of resources and increasingly severe environmental problems, lightweight materials such as aluminium alloys are widely used in the manufacturing of structural components for aerospace applications owing to their excellent properties that assist with weight reduction [1][2][3]. Methods that can be used to spot-weld aluminium alloys include resistance spotwelding (RSW) [4], laser spot-welding (LSW) [5], friction stir spot-welding (FSSW) [6,7], riveting [8], and refill friction stir spot-welding (RFSSW) [9]. Fabrication of lap joints of dissimilar aluminium structural components with unequal thickness, such as joining of a handle of 5xxx Al to a plane skin of 2xxx Al, generally proceeds using a joining technique.…”
Section: Introductionmentioning
confidence: 99%
“…The RFSSW welding tool consists of three components [26]: a pin with diameter of 5.2 mm, a sleeve with an external diameter of 9 mm and a clamping ring. The detailed procedure of the re ll friction stir spot welding process can be found in previous papers by the authors [23,26]. In general, the welding procedure consists of four steps touchdown, plunging, re lling and tool retraction.…”
Section: Rfssw Proceduresmentioning
confidence: 99%
“…It was found that hook height and joint integrity are the key parameters in uencing load capacity of the joints. RFSSW is commonly used to join various grades of aluminium alloys used in the aerospace and automotive industries [23,24]. Takeoka et al [25] developed scrubbing RFSSW (sc-RFSSW) to join non-coated mild steel and aluminium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, friction stir welding (FSW) was initially introduced by TWI in the United Kingdom as a newly developed solid-state welding process, particularly for joining aluminum alloys with specific requirements that should be fulfilled [1,2]. Then friction stir spot welding (FSSW) was developed as one of its variant for local joining of similar and dissimilar sheets [3][4][5][6][7][8][9] as a promising technique with similarities to the basic concepts of linear FSW with a specific requirement where no lateral movement of the tool is required [10]. More interestingly, the rotating tool pierces the sheets that are being welded and then produces a stir zone.…”
Section: Introductionmentioning
confidence: 99%